Peningkatan Kesadaran Ibu Tentang Gizi Seimbang melalui Edukasi Gizi Guna Menekan Angka Stunting di Ds. Jambu, Kec. Jambu, Kab. Semarang - Istadea Anjani; Rifka Eriana Saputri; Shafa Kayyah Salsabila; Alif Deri Mahendra; Nabilatun Nisa; Nurul Irsyadah; Muhammad Syukron Abdul Fatah (Lembaga Pengembangan Kinerja Dosen, 2025)
Toddlers are in an important stage of growth and development. During this period, rapid growth and development are greatly influenced by adequate nutritional intake. One of the health problems that toddlers can experience is stunting, which is a growth disorder caused by long-term malnutrition. Stunting can affect brain development, reduce cognitive abilities, and increase the risk of chronic diseases later in life. Based on data from the 2022 Indonesian Nutritional Status Survey (SSGI), the prevalence of stunting in Indonesia is still high, although there has been a decline. Mothers have a very important role in monitoring and providing adequate nutrition for children. It is hoped that by increasing mothers' knowledge about nutrition, stunting can be prevented so that superior human resources are created in the future.